Residential demand response considering distributed PV consumption: A model based on China's PV policy. (1st April 2019) - Lu, Qing; Yu, Hao; Zhao, Kangli; Leng, Yajun; Hou, Jianchao; Xie, Pinjie
Abstract: Household distributed photovoltaic (PV) can supply clean power directly to the end users. With the rapid growth of the distributed PV installed capacity, the problems of PV grid connection and PV consumption are becoming more and more serious in China. It is an effective means to improve the efficiency of PV system by promoting the home self-consumption of PV generation. In this study, a residential demand response model considering distributed PV consumption based on dynamic electricity price is proposed. The household users are classified into several types with different power consumption preferences in this model. Both the comfort and economy of power consumption are quantified to describe the users' satisfaction. The model is established with two goals, maximizing the users' satisfaction meanwhile minimizing PV power into the grid. Then a solution algorithm based on NSGA-II is proposed to solve the model. Finally, an example study based on China's PV policy is presented, and the results show that the model has certain advantages in improving the users' satisfaction and increasing the rate of self-consumption of PV generation. In addition, sensitivity analysis of the provincial government's PV subsidies in China is also carried out and the relevant policy recommendations are presented. Highlights: Household users are classified into several types with different preferences. The UEV with users' power consumption comfort and economy is designed. Exploiting the interaction between users and the power grid for PV consumption. Sensitivity analysis of the provincial government's PV subsidies in China.